Analisis Risiko Penyakit Paru Obstruksi Kronis Akibat Paparan Debu Pm2.5 pada Pekerja Mebel Kayu CV Mekar Baru Kota Padang - Dhinie Anjelicha; Muchsin Riviwanto; Wijayantono Wijayantono (Poltekkes Kemenkes Padang, 2022)
Particulate matter 2.5 (particulate dust 2.5) is a particle with an aerodynamic diameter of less than 2.5 m. The presence of PM2.5 dust in wood dust in the air can be inhaled into the respiratory tract and deposited into the alveolus to the lungs. Long-term risks of these particulates can cause chronic lung disease to lung cancer. The purpose of this study was to determine the risk analysis of COPD due to PM2.5 dust exposure on wood furniture workers CV. Mekar Baru, Padang City in 2021. The research design uses the Environmental Health Risk Analysis (ARKL) method. The samples taken were air samples with a size of 2.5 micrometers and a sample of 16 workers. The results of this study are a potential source of activity that contains PM2.5 elements from sawing and sanding and painting activities with a PM2.5 concentration of 0.067 mg/m3 in the process. sawing and sanding and 0.32 mg/m3 in the painting process. . The results of COPD disorders (Chronic Obstructive Pulmonary Disease) in furniture industry workers are 73.3% of workers experiencing COPD symptoms. 33% at risk. Suggestions from this study are that workers are expected to wear personal protective equipment (PPE) at work to reduce the danger of exposure to dust that enters the body.